Late Wisconsinan glaciation of the Glenlyon Range, Pelly Mountains, Yukon Territory, Canada - Ward, Brent C.; Jackson Jr., Lionel E. (Canadian Journal of Earth Sciences, 1992)
Airphoto analysis, identification of erratics, and stratigraphic and geomorphic investigations were used to determine the nature of McConnell (Late Wisconsinan) age glaciation in the Glenlyon Range, Yukon Territory. Most of the peaks of the Glenlyon Range were nunataks within the Selwyn Lobe of the Cordilleran Ice Sheet. The configuration of local and Selwyn Lobe moraines indicates that local glaciers did not extend beyond the cirques and made no contribution to the Selwyn Lobe. These conclusions are confirmed by the character of sediments examined in sections along Little Sheep Creek and by the distribution of erratics in one of the cirque valleys. Aridity limited local ice growth; large glaciers did not grow because of insufficient precipitation.